2008
DOI: 10.1136/ard.2008.091611
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in rheumatoid arthritis patients 1 year after adalimumab therapy: arrest of bone loss

Abstract: Objective:To explore the effects of anti-tumour necrosis factor (TNF)α antibody therapy on bone mineral density (BMD) of the lumbar spine and femur neck in patients with rheumatoid arthritis (RA).Methods:A total of 50 patients with active RA (DAS28⩾3.2) who started adalimumab (40 mg subcutaneously/2 weeks) were included in an open label prospective study. All patients used stable methotrexate and were allowed to use prednisone (⩽10 mg/day). The BMD of the lumbar spine and femur neck was measured before and 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
85
1
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 13 publications
10
85
1
16
Order By: Relevance
“…In contrast, prospective open studies show that complete control of inflammation (in parallel with clinical improvement and thus increased mobility) is accompanied by the absence of bone loss. 56 This is expected in SpA in the absence of GCs, but is also observed in RA of the hand, spine and hip, in patients receiving low doses of GCs. [56][57][58] In the BeSt study, conducted in patients with recent-onset active RA, bone loss was limited in all treated groups, including in the group initially treated with high-dose prednisone.…”
Section: Role Of Fraxmentioning
confidence: 96%
“…In contrast, prospective open studies show that complete control of inflammation (in parallel with clinical improvement and thus increased mobility) is accompanied by the absence of bone loss. 56 This is expected in SpA in the absence of GCs, but is also observed in RA of the hand, spine and hip, in patients receiving low doses of GCs. [56][57][58] In the BeSt study, conducted in patients with recent-onset active RA, bone loss was limited in all treated groups, including in the group initially treated with high-dose prednisone.…”
Section: Role Of Fraxmentioning
confidence: 96%
“…Результаты контролируемых клинических и открытых исследований позволяют заключить, что подкожное вве-дение адалимумаба эффективно и безопасно как при РА, анкилозирующем спондилите и псориатическом артрите у взрослых пациентов [10][11][12][13][14][15][16][17][18][19][20][21][22], так и при ЮИА у детей [23][24][25][26][27][28][29][30][31][32][33][34][35]. Соответственно, в случае первичной или вторич-ной неэффективности других генно-инженерных биологи-ческих препаратов переключение на адалимумаб может оказаться перспективным.…”
Section: Introductionunclassified
“…The results of controlled clinical trials and open studies demonstrated that subcutaneous administration every two weeks of the drug is safe and effective in adult patients with rheumatoid and psoriatic arthritis [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], as well as in children with juvenile idiopathic arthritis and uveitis [49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%